Exploring the role of artificial intelligence (AI) innovation in economic performance: Evidence from East Asia - Abid, Ihsen (International Journal of Innovative Research and Scientific Studies, 2025)
This study investigates the impact of artificial intelligence (AI) innovation on economic growth in East Asia (China, Japan, and South Korea) from 2010 to 2023, using AI patent filings as a proxy for technological advancement. A panel data approach is employed, incorporating fixed effects, random effects, and pooled ordinary least squares (OLS) models to examine the relationship between AI innovation and GDP growth. Panel cointegration tests assess long-run equilibrium relationships, while the Granger non-causality test determines the direction of causality. The results indicate that AI innovation significantly contributes to GDP growth, reinforcing the role of technological progress in economic expansion. Trade openness is also positively associated with economic performance. However, gross capital formation exhibits a counterintuitive negative effect, suggesting inefficiencies in capital allocation or diminishing returns. Inflation has a mild yet statistically significant impact on growth. This study provides empirical evidence on the role of AI-driven innovation in shaping East Asian economies. The findings offer valuable insights for policymakers, emphasizing the need for strategies that enhance AI adoption, optimize capital investment, and leverage trade to sustain economic growth in the AI era.